Pyridostigmine Mitigates Methotrexate-Induced Liver Fibrosis in Rats: Association with Changes in BMP-9, SIRT1, and Endoglin Expression - Mehmet Ulusan; Mumin Alper Erdogan; Ozkan Simsek; Hilal Ustundag; Zafer Dogan; Bertug Bekir Ciftci; Mesih Kocamuftuoglu; Imdat Orhan; Oytun Erbas (Biomedicines, 2025)
Background and Objectives: Methotrexate (MTX) is a widely utilised pharmaceutical agent in the treatment of various malignancies and inflammatory diseases. However, its clinical utility is often constrained by its potential for hepatotoxicity. Although pyridostigmine is a well-established reversible acetylcholinesterase inhibitor, its potential therapeutic role in preventing hepatic injury remains incompletely defined. The present study aimed to investigate whether pyridostigmine provides protective effects against MTX-triggered liver damage in a rat model. Methods: Thirty-six female Wistar albino rats randomly assigned to three groups: control (n = 12), MTX + saline (n = 12), and MTX + pyridostigmine (n = 12). Hepatotoxicity was induced by a single-dose MTX injection (20 mg/kg), followed by daily oral administration of either pyridostigmine (5 mg/kg) or saline for ten consecutive days. Hepatic function markers, oxidative stress parameters, fibrosis-associated mediators, and histopathological changes were assessed. Results: Pyridostigmine significantly attenuated MTX-induced elevations in plasma alanine aminotransferase (p < 0.05) and cytokeratin-18 levels (p < 0.001), and reduced liver and plasma malondialdehyde (MDA) levels (p < 0.05). Additionally, pyridostigmine treatment resulted in reduced levels of transforming growth factor-beta (p < 0.05), bone morphogenetic protein-9 (p < 0.001), and endoglin levels (p < 0.05), as well as increased sirtuin 1 level (p < 0.05). Histopathological examination revealed that pyridostigmine treatment significantly reduced MTX-induced hepatocyte necrosis, fibrosis, and cellular infiltration. Conclusions: Pyridostigmine exerted hepatoprotective effects against MTX-induced liver injury by attenuating oxidative stress, restoring SIRT1 expression, and suppressing pro-fibrotic signaling. These findings indicate that pyridostigmine may hold therapeutic potential for the prevention of MTX-associated hepatotoxicity.